2021
DOI: 10.1038/s41598-021-99894-6
|View full text |Cite
|
Sign up to set email alerts
|

Serum vitamin D status inversely associates with a prevalence of severe sarcopenia among female patients with rheumatoid arthritis

Abstract: Sarcopenia is an age-related disease with an increased risk of mortality. It is emerging that low serum 25-hydroxyvitamin D [25(OH)D] affects the sarcopenic state in general, but in rheumatoid arthritis (RA), these associations are not understood although the prevalence of vitamin D insufficiency is high in RA. We conducted a cross-sectional study of older female outpatients from our cohort (KURAMA) database. We measured skeletal muscle mass, handgrip strength, and gait-speed to diagnose severe sarcopenia. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…In line, in animal models, diet-induced vitamin D deficiency leads to the manifestation of sarcopenia symptoms in skeletal muscles, including muscle weakness, decreased muscle force and physical performance, and reduced mitochondrial activity [ 129 , 135 , 136 , 137 , 138 ]. Moreover, reduced vitamin D levels have been associated with decreased muscular mass and strength in different human cohorts [ 139 , 140 , 141 , 142 ]. Despite these association studies and the biological plausibility of the link between vitamin D and muscle health, intervention studies are conflicting.…”
Section: Vitamin Dmentioning
confidence: 99%
“…In line, in animal models, diet-induced vitamin D deficiency leads to the manifestation of sarcopenia symptoms in skeletal muscles, including muscle weakness, decreased muscle force and physical performance, and reduced mitochondrial activity [ 129 , 135 , 136 , 137 , 138 ]. Moreover, reduced vitamin D levels have been associated with decreased muscular mass and strength in different human cohorts [ 139 , 140 , 141 , 142 ]. Despite these association studies and the biological plausibility of the link between vitamin D and muscle health, intervention studies are conflicting.…”
Section: Vitamin Dmentioning
confidence: 99%
“…It has recently been found that patients with RA have lower levels of vitamin D than patients without RA [ 106 ]. Additionally, it has been reported that, in patients with RA, low levels of vitamin D are related to severe sarcopenia and poor physical performance [ 107 ]. The reason this association exists is because vitamin D participates in the regulation of oxidative stress and calcium homeostasis, the suppression of cytokines and macrophages, and the promotion of the differentiation of regulatory T cells [ 107 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, it has been reported that, in patients with RA, low levels of vitamin D are related to severe sarcopenia and poor physical performance [ 107 ]. The reason this association exists is because vitamin D participates in the regulation of oxidative stress and calcium homeostasis, the suppression of cytokines and macrophages, and the promotion of the differentiation of regulatory T cells [ 107 ]. On the other hand, in a study conducted in mice with induced muscular dystrophy, the inhibition of myostatin through the expression of the follistatin transgene resulted in early improvements in histopathology, but, in the long term, muscle degeneration increased [ 108 ].…”
Section: Discussionmentioning
confidence: 99%
“…The secondary causes of sarcopenia result from comorbidities that affect the patient's osteo-arthro-muscular triad or the bio-psycho-social triad in some way, leading to poor quality of life (QoL). There is abundant literature to support the osteo-arthro-muscular triad [ [23] , [24] , [25] , [26] , [27] , [28] ] or the bio-psycho-social triad [ [29] , [30] , [31] , [32] ] comorbidities as a cause of secondary sarcopenia. Corresponding literature from South Asia includes an article from Pakistan, that mentions that major depression is associated with low QoL and leads to sarcopenia with loss of muscle mass and function [ 33 ].…”
Section: Sarcopenia As a Syndromementioning
confidence: 99%